The perception of pediatric sickle cell anemia patient's caregivers toward hematopoietic stem cell transplantation (single-center experience, Saudi Arabia) - Monagel, Dania A.; Alemam, Naglla; Betar, Manar; Alnafisi, Fay N.; Faidah, Dania E.; Aloteibi, Reema E.; Khan, Muhammad; Malli, Israa A. (Frontiers in Pediatrics, 2023)
Background: Sickle cell disease (SCD) is a relatively common genetic disorder in Saudi Arabia characterized by the predominance of sickle hemoglobin (HbS). Although multiple supportive care options exist for patients with SCD, hematopoietic stem cell transplantation (HSCT) is the only cure available and has become highly successful, with an almost 91% overall survival rate. However, pursuing this procedure is still restrained as a curative treatment option. Therefore, this study aimed to evaluate the perception of parents’ caregivers at the National Guard Hospital pediatric hematology clinic regarding using HSCT as a curative approach for their children with SCD. Methods This is a cross-sectional study of the interviewer-administered survey distributed utilizing electronic devices to caregivers of pediatric patients with SCD. Subjects were recruited from Pediatric Hematology & Oncology clinics at National Guard Hospital Affairs in King Abdulaziz Medical City, Jeddah, Saudi Arabia. An estimated sample size of 100 was initially calculated out of 140 pediatric SCD patients; 72 responses were collected from participants. All study participants gave informed consent. All results were analyzed using SPSS; moreover, statistics were set at a CI of 95% and a p < 0.05. In addition, inferential and descriptive statistics were done. Results Of all respondents, 42 (67.8%) would accept HSCT if their hematologist recommended it. However, approximately 7 (11.3%) were not interested in the procedure, and the rest ,13 (21%), were uncertain. The most reported reasons for HSCT rejection among all respondents were attributed to side effects 31 (50.8%), lack of knowledge 8 (13.1%), and misconception toward the procedure 22 (36.1%). Conclusion The results of this study were consistent with the fact that most caregivers would follow along with HSCT if it seemed to be fit and was recommended by their hematologists. However, to the best of our knowledge, our study being the first of its kind in the region, further research in the kingdom on the perception of HSCT is needed. Nonetheless, further patient education, an increase in caregivers’ knowledge, and enlightenment of the medical team on HSCT as a curative option for sickle cell disease are vital.